Assessing an LGBTQ Responsive Training Intervention for School Counselor Trainees. Issue 2 (4th May 2017) - Luke, Melissa; Goodrich, Kristopher M.
Abstract : This mixed methods, explanatory sequential design study explored changes over time in participants who were taking part in an experiential training intervention focused on school counseling trainees' knowledge, awareness, and skills in working with P–12 lesbian, gay, bisexual, transgender, and questioning (LGBTQ) student populations. Results indicated that trainees' knowledge, skills, and school counseling–related self-efficacy with P–12 LGBTQ student populations increased over time, but trainees' reported levels of sexual orientation awareness decreased. Implications for training, practice, and research are discussed.